PENGARUH PENGGUNAAN GADGET TERHADAP MINAT BELAJAR EKONOMI SISWA KELAS X DI SMA NEGERI 7 BONE - Uni Lestari, Ika; Hamka; Azis, Emmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the effect of gadget use on students' learning interest in economics of Grade X students at SMA Negeri 7 Bone. A quantitative approach with an ex post facto design was employed. The population consisted of 145 Grade X students, and the sample consisted of 50 students selected through proportional random sampling. Data were collected using a five-point Likert scale questionnaire covering gadget use and learning interest, and analyzed using validity testing, reliability testing (Cronbach's Alpha = 0.950), normality testing, linearity testing, and simple linear regression with the aid of IBM SPSS version 26. The results showed the regression equation Y = 37.795 + 0.732X, with t-count = 2.906 greater than t-table = 1.677 and a significance value of 0.006 (< 0.05), so that H0 was rejected and H1 was accepted. The coefficient of determination (R²) was 0.150, indicating that gadget use contributed 15.0% to the variation in students' learning interest in economics, while the remaining 85.0% was explained by other variables. Thus, it can be concluded that gadget use has a positive and significant effect on students' learning interest in economics of Grade X students at SMA Negeri 7 Bone. Keywords: Gadget 1, Learning Interest 2